New insights into the biology of Calanus spp. (Copepoda) males in the Arctic - Daase, Malin; Kosobokova, Ksenia; Last, Kim S.; Cohen, Jonathan H.; Choquet, Marvin; Hatlebakk, Maja Karoline Viddal; Søreide, Janne E. (Marine Ecology Progress Series, 2018)
publishedVersion Paid Open Access